The cow that went oink - Most, Bernard (San Diego : Harcourt Brace Jovanovich, 1994)
A cow that oinks and a pig that moos are ridiculed by the other barnyard animals until each teaches the other a new sound.
G1
Keywords: Animal sounds -- Fiction; Domestic animals -- Fiction